2007
DOI: 10.1021/jo0708590
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrating Dynamic [2]Rotaxanes

Abstract: Upon mixing and dehydration, 2,6-diformylpyridine and 2,2'-oxybis(ethylamine) form a dynamic combinatorial library of at least nine members. Through hydrogen bonding and other intermolecular interactions, templating dumbbell molecules select one macrocyclic member of the library, at the expense of all the others, to create [2]rotaxanes. These rotaxanes, however, retain the dynamic character of the library, since a diformylpyridine analogue can exchange with the macrocyclic component in solution. In addition, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 66 publications
1
22
0
1
Order By: Relevance
“…The solid-state structure fora na nalogous derivativeo ft he dialdehyde 2 also displays aWshape. [20] Reaction of dialdehyde 1w ith the diamine N 2 Oinp resence of cadmium ions-metal-templated formation of the macrocyclic complex Cd·(1·N 2 O).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The solid-state structure fora na nalogous derivativeo ft he dialdehyde 2 also displays aWshape. [20] Reaction of dialdehyde 1w ith the diamine N 2 Oinp resence of cadmium ions-metal-templated formation of the macrocyclic complex Cd·(1·N 2 O).…”
Section: Resultsmentioning
confidence: 99%
“…9-10). [20] Reaction of dialdehyde 2w ith the diamine N 2 O 3 in presence of cadmium ions-metal-templated formation of the macrocyclic complex Cd·(2·N 2 O 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the two step condensation-reduction process, they obtained the desired [2]rotaxane in 70% yield after standard column chromatography. Stoddart et al used this strategy later on to assemble mechanically interlocked dendrimers [61], long rotaxaneoligomers [62] and to study the dynamics of reversible rotaxanes through imine bond formation [63].…”
Section: Rotaxane Formation Through Macrocycle Ring-closing Reactionsmentioning
confidence: 99%
“…A DCL was created57 in our research laboratories by refluxing 2,2′‐oxybis(ethylamine) with 2,6‐diformylpyridine in toluene (Scheme ) under Dean–Stark conditions. Mass spectrometry revealed that the DCL contains at least nine members, one of which is a [24]crown‐8‐like macrocycle.…”
Section: Imine Bondsmentioning
confidence: 99%